2002
DOI: 10.1038/sj.bjc.6600041
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early pregnancy following chemotherapy on disease relapse and foetal outcome in women treated for gestational trophoblastic tumours

Abstract: Little literature exists on the safety of early pregnancy following chemotherapy. Here we assess the rate of relapse and foetal outcome in women who have completed single and multi-agent chemotherapy for gestational trophoblastic tumours. The records of 1532 patients treated for persistent gestational trophoblastic tumours at Charing Cross Hospital between 1969 and 1998 were reviewed. Patients were defined as receiving single agent or multi-agent treatment. Relapse rates and foetal outcome were reviewed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 23 publications
2
11
1
Order By: Relevance
“…Except from Hodgkin's disease, where no clear conclusions can be drawn [2,[6][7][8][9][10], most of the studies on reproductive performance of women treated with anticancer drugs have described no increase in the incidence of infertility, prematurity, stillbirths or congenital malformations. The influence of the specific agents used on fertility and pregnancy outcomes is culled from studies including women treated for gestational trophoblastic tumour [11][12][13][14][15][16][17][18][19][20][21], ovarian carcinoma [22][23][24][25], and breast [26][27][28][29]. The results of our survey are in accordance with those studies.…”
Section: Discussionsupporting
confidence: 90%
“…Except from Hodgkin's disease, where no clear conclusions can be drawn [2,[6][7][8][9][10], most of the studies on reproductive performance of women treated with anticancer drugs have described no increase in the incidence of infertility, prematurity, stillbirths or congenital malformations. The influence of the specific agents used on fertility and pregnancy outcomes is culled from studies including women treated for gestational trophoblastic tumour [11][12][13][14][15][16][17][18][19][20][21], ovarian carcinoma [22][23][24][25], and breast [26][27][28][29]. The results of our survey are in accordance with those studies.…”
Section: Discussionsupporting
confidence: 90%
“…The increased risk of miscarriage and stillbirth reported by some authors 18,20 is not confirmed by our data; all the patients in our study, however, conceived at least 12 months after the end of treatment. Pregnancy delay to at least 12 months after chemotherapy completion should be recommended to all patients to allow optimal surveillance and early tumor relapse detection.…”
Section: Discussioncontrasting
confidence: 86%
“…Blagden et al 18 reported a higher miscarriage rate in patients conceiving within 12 months after combination chemotherapy. We cannot compare these results with ours because all patients in our study completed follow-up before conception.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of congenital abnormality was low (1.8%), irrespective of the type of chemotherapy used. 63 The rate of stillbirth was elevated compared with the normal population (18.6 in 1000 births). 64 However, in another UK study of 241 treated patients who had a pregnancy within 12 months of chemotherapy, there was no significant increased risk of miscarriage, ectopic pregnancy, second molar pregnancy or stillbirth compared to the general UK population.…”
Section: Evidence Level 2+mentioning
confidence: 98%